2019
DOI: 10.17240/aibuefd.2019.19.49440-478714
|View full text |Cite
|
Sign up to set email alerts
|

Okul Öncesi̇ Dönem Çocuklarinin Ki̇şi̇ler Arasi Problem Çözme Ve Sosyal Beceri̇leri̇ İle Akran İli̇şki̇leri̇ni̇n Değerlendi̇ri̇lmesi̇

Abstract: ÖZBu araştırmanın amacı sosyal beceri puanı en düşük ve en yüksek olan okul öncesi dönem çocuklarının kişilerarası problem çözme becerilerinin ve arkadaşlık ilişkilerinin değerlendirilmesidir. Bu amaç doğrultusunda araştırmada, nitel ve nicel verilerin harmanlandığı karma yöntem kullanılmıştır. Çalışma grubunu okul öncesi eğitim almakta olan 17'si 48-60 ay, 92'si ise 60-72 ay olan 57 kız ve 52 erkek çocuk olmak üzere toplam 109 çocuk oluşturmaktadır. Araştırmanın sonucunda çocukların sosyal becerisi ile sosyal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In his study which psychosocial development based education program was conducted, Şahin (2015) found that children with high problem solving skills scores had also high emotional intelligence scores. Dinçer, Baş, Teke, Aydın, İpek and Göktaş (2019) conducted a study to assess interpersonal problem-solving skills and friendship relationships of preschool children with the lowest and highest social skills scores, and found a statistically significant negative correlation between the social skills and non-social peer solutions of children. In other words, children with high social skills displayed more positive behaviors in their peer relationship while children with low social skills preferred more negative methods and behaviors in their peer relationships.…”
Section: Discussionmentioning
confidence: 99%
“…In his study which psychosocial development based education program was conducted, Şahin (2015) found that children with high problem solving skills scores had also high emotional intelligence scores. Dinçer, Baş, Teke, Aydın, İpek and Göktaş (2019) conducted a study to assess interpersonal problem-solving skills and friendship relationships of preschool children with the lowest and highest social skills scores, and found a statistically significant negative correlation between the social skills and non-social peer solutions of children. In other words, children with high social skills displayed more positive behaviors in their peer relationship while children with low social skills preferred more negative methods and behaviors in their peer relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Since preschool institutions are places where children experience social roles outside of the family and acquire the necessary social skills to live in society, the relationship established with peers can come to the fore in this period (Solak Arabacı & Demircioğlu, 2019). Communication between children and their peers in this period can help them develop problem-solving and coping skills (Dinçer et al, 2019). Although the importance of peer relationships is acknowledged, not all children are able to maintain their peer relationships properly in the preschool period and they may experience failure in this social role by being excluded by their peers.…”
Section: Extended Abstract Introductionmentioning
confidence: 99%